Ambivalent methods, geographical difference, and the politics of feeling-knowing. Issue 1 (March 2021) - Ruez, Derek; Cockayne, Daniel
We offer an engagement with the generous responses to our article, 'Feeling Otherwise'. We think with the authors who responded to our paper to sketch out an affirmative way to understand the concept of ambivalence. We clarify key points, reflect on the responses, and make suggestions for ways to explore this topic further.